The Role of Institutional Development in Education System: R&D and Innovation and their Impact on Economic Growth (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The aim of this paper is to provide a closer look of the institutional development in educational system and its impact on economic growth. Accumulation of human capital and technological development are factors that are considered to be crucial for economic growth. Thus, investing in education, R&D and innovation is essential for a country’s prospects for economic growth. However, the main idea is to present this topic from institutional point of view. By using literature and statistical analysis, the paper investigates whether the degree of institutional development in country’s educational system is sufficient enough to create prospects for economic growth. We compare 4 different countries, Macedonia and Serbia, non EU countries and Bulgaria and Slovenia member countries of the EU. The research findings indicate to the fact that institutionalized society with higher degree of institutional development in this case in the educational system is more likely to boost the economic growth. The results also indicate to the fact that societies in which the degree of institutional development is higher, as it is in our case in Slovenia and Bulgaria, are more likely to produce well qualified and skilled labour force which will further impact the economic growth.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.